ANALISIS MUTASI, KOMPENSASI DAN PENGEMBANGAN KARIR TERHADAP TURNOVER INTENTION PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA DIREKTORAT JENDERAL BEA DAN CUKAI - Handaya, Setia; Suyanto; Jayadi; Indri Astuti (Jurnal Manajemen, 2023)
The Directorate General of Customs and Excise (DGCE) has substantial human resources. Based on data as of 1 December 2022, the number of DGCE employees is 16,149 people and were spread across 20 regional offices and 3 main service offices throughout the territory of the Republic of Indonesia. Based on employee profiling data conducted in March 2023, 72% of these employees are employees who have home bases in Java. By considering various aspects DGCE carries out job rotation process and career development for these employees. This study aims to analyse the effect of job rotation, compensation, and career development on turnover intention with job satisfaction as an intervening variable at the DGCE. This research is based on several previous studies which show that job satisfaction can influence the relationship between job rotation, career development, and turnover intention. The research method used is quantitative research using a survey (questionnaire) as a data collection instrument. Respondents in this study were employees at the DGCE who were spread throughout the territory of the Republic of Indonesia with positions from general inspector to supervisor and functionally equivalent. The research sample was taken as many as 3.813 respondents. The collected data will be analysed using the validity test, reliability test, and Sobel test. The results of this study are expected to provide an overview of the effect of job rotation and career development on turnover intention with job satisfaction as an intervening variable at the DGCE.